ANALISA DISTRIBUSI TEMPERATUR INTERMEDIATE TANK FASSIP-07 MENGGUNAKAN METODE COMPUTATIONALFLUID DYNAMICS (CFD) - Prasetio, Dimas; Zuliantoni; Juarsa, Mulya; Ismarwanti, Sri; Kharisma, Sunandi (UNIB Press, 2025)
This study aims to understand the temperature distribution in the natural circulation system in the Intermediate Tank FASSIP-07 using the Computational Fluid Dynamics (CFD) method. Simulations were performed using Ansys Workbench R1 2024 software, with inlet temperature variations of 70°C, 80°C, and 90°C. The results showed that the highest temperature distribution was found at the inlet with a temperature of 90°C, while the outlet reached the lowest temperature at 70°C. This conclusion was obtained from the analysis of fluid flow driven by the buoyancy phenomenon due to differences in density. This study shows the potential for using a passive cooling system for nuclear reactors to improve safety in emergency conditions.